Pengelolaan Kelas Berbasis Multikultural di TK Nur Miyazaki Islamic Chracter School - Rolyke Gonie; Muhammad Akil Musi; Herman (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
Indonesia, as a multicultural country, faces a variety of differences that lead to conflicts such as violence, oppression, and identity crisis. Plurality, which is a source of national strength, can at any time turn into a trigger for conflict if there is no understanding, tolerance and mutual understanding in addressing differences. Even in one class there are various kinds of differences and the classroom teacher is an important control holder in managing gender diversity, social status, ethnicity, and even intelligence diversity in the classroom. This study aims to understand multicultural-based classroom management strategies at the early childhood education level. Using a descriptive qualitative approach as a method of research. The place where the research was conducted was in one of the PAUD foundations named Nur Miyazaki Islamic Character School Kindergarten. Researchers made observations and conducted interviews with the Principal and class B teachers as data sources. Through the results of the study, it can be seen that the teacher's strategy of managing gender diversity, social status diversity, ethnic diversity, and social status diversity in the classroom is effective in developing the character of caring, sharing, tolerance, responsibility, and willingness to cooperate with one child with another. Although sometimes children respond with resistance to the new habit, the teachers successfully manage the children's emotions well.